PROBLEMATIKA PENEGAKAN HUKUM PIDANA LINGKUNGAN DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP DAN KUHP 2023 - Siti Nurvinia Nareswari; Hilman Nur (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
Environmental pollution is a serious issue affecting ecosystem sustainability and public health. Industrial activities without proper waste management are a major cause of pollution, including water, air, and soil contamination. This condition not only causes environmental damage but also leads to social and economic losses for communities. Therefore, strict and effective law enforcement is required to create a deterrent effect and prevent similar actions. This study aims to examine the regulation of environmental crimes based on Law Number 32 of 2009 concerning Environmental Protection and Management and to analyze law enforcement against offenders from the perspective of the Indonesian Criminal Code (KUHP) 2023. The research method used is normative juridical with statutory and conceptual approaches through literature study. The results show that the 2023 Criminal Code provides a more comprehensive legal basis, particularly regarding corporate criminal liability. However, in practice, law enforcement still faces challenges such as weak supervision and difficulties in proving cases. Therefore, it is necessary to strengthen supervision and ensure consistent law enforcement to achieve optimal environmental protection